2012
DOI: 10.1016/j.rbmo.2011.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized trial of multiple micronutrients in subfertile women undergoing ovulation induction: a pilot study

Abstract: This study investigated whether subfertile women undergoing ovulation induction using standard treatment regimens with clomiphene citrate/gonadotrophins have higher pregnancy rates when on an adjuvant multiple micronutrient (MMN) nutritional supplement compared with folic acid alone. A prospective randomized controlled trial was conducted in a teaching-hospital fertility clinic on 58 subfertile women, of which 56 women completed the study. Women undergoing ovulation induction were allocated to either receive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…One pilot study found Pregnancycare was associated with higher pregnancy rates in subfertile/infertile women undergoing ovulatory induction [20] but none of the Pregnancycare reviewers on Amazon reported using Clomid or other ovulatory induction treatments. Another low-power study reports higher pregnancy rates among 53 FertiliBlend users who had previously tried to conceive for 6-36 months [21] but, in the absence of follow-up studies with greater power, it is difficult to ascertain if this difference between treatment groups was clinically meaningful.…”
Section: Methodsmentioning
confidence: 99%
“…One pilot study found Pregnancycare was associated with higher pregnancy rates in subfertile/infertile women undergoing ovulatory induction [20] but none of the Pregnancycare reviewers on Amazon reported using Clomid or other ovulatory induction treatments. Another low-power study reports higher pregnancy rates among 53 FertiliBlend users who had previously tried to conceive for 6-36 months [21] but, in the absence of follow-up studies with greater power, it is difficult to ascertain if this difference between treatment groups was clinically meaningful.…”
Section: Methodsmentioning
confidence: 99%
“…This molecule, as demonstrated by some studies [14, 15], seems to be able to work in synergy in all forms of PCOS, both in those induced by insulin resistance and in cases of tissue oxidative stress.…”
Section: Discussionmentioning
confidence: 85%
“…To determine whether there is a superior treatment regimen for infertile patients, several studies have been conducted to compare the efficacy of different kinds of antioxidants in the past few years [29], but little attention has been given to female infertility [24] and none have addressed PCOS. One prospective randomized trial investigated whether a subordinate multiple micronutrient (MMN) supplementation providing folic acid, vitamin B, vitamin E, vitamin C, zinc, selenium, vitamin A and other multivitamins/minerals could benefit women with anovulatory infertility or unexplained infertility who were undergoing ovulation induction by the standard treatment regimen with CC and HMG [30]. It was observed that women on MMN supplementation had a significantly higher cumulative clinical pregnancy rate and ongoing pregnancy rate compared with those who were on folic acid alone.…”
Section: Discussionmentioning
confidence: 99%